Bulid campus network authentication system based on centralized 802.1x - Bin LIU; Yu-zhi HE; Yong ZHANG (Tongxin xuebao)
802.1x authentication was usually distributed deployment.However,With the expansion of the campus net-work and increasement of the number of control devices,the management of equipment and authentication system be-come so inconvenience.On the other hand,centralized 802.1x could not locate the terminal.The problem of terminal lo-cation under centralized 802.1x was solved by using （NAS IP,Port,Vlan）three tuple,Super Vlan and dynamic address allocation technology.Centralized 802.1x authentication system was tested in the of Huazhong Science and Technology University campus network,and achieved good results.